Embedding scenarios of Austria's transition to climate-neutral economy within the context of global action to mitigate climate change. EconTrans working paper #2 - Piotr Zebrowski; Matthias Jonas (Austrian Institute of Economic Research (WIFO), 2021)
In this working paper we place scenarios of Austria's transition to a green economy in a global context of efforts of international community to limit global warming to the levels outlined in the Paris Agreement. To this end we propose a method of deriving robust and physically grounded budgets of Austria's cumulative GHG emissions that are consistent with the 1.5 êC and the 2 êC warming targets of Paris agreement, respectively. These budgets are based on the most recent estimates of carbon budgets for the 1.5 êC and 2 êC warming targets and delineate a "space for manoeuvre" within which Austria's green transformation must take place if it is to make a desired contribution to humanity's climate-change mitigation efforts. We also derive reference pathways for Austria's GHG emissions that are in line with the 1.5 êC and the 2 êC warming targets, and which inform us about the necessary emission reductions in any given year, e.g., in 2050. We also demonstrate how budgets of cumulative national GHG emissions and corresponding reference emission pathways can be downscaled to provide boundary conditions for a novel approach to modelling economic transformations based on the concept of functionalities. First, we establish how much of GHG emissions is currently caused by providing functionalities Access, Shelter and Other Life Support in Austria. Next, with help of existing EU-wide scenarios of green transition that resolve multiple economic sectors, we assess expected cumulative emissions from sectors not covered by these functionalities. Finally, we subtract these cumulative emissions from the budget of Austria's total GHG emissions and distribute the remainder between the considered functionalities.
Keywords: 330